Pan and tilt surveillance camera system - 188286 Aw, Khai Liang (Skudai : Universiti Teknologi Malaysia, 2002)
Project Paper (Bachelor of Electrical Engineering (Mechatronics)) - Universiti Teknologi Malaysia, 2002